2018
DOI: 10.17219/dmp/80944
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors in oroantral communication while extracting the upper third molar: Systematic review

Abstract: The removal of the upper third molar is a procedure commonly performed in oral and maxillofacial surgery. Maxillary third molars are generally less difficult to extract than mandibular third molars. The surgical removal of maxillary third molars is usually associated with low complication rates and low morbidity. This procedure involves the risk of developing complications such as oroantral communication, displacement into adjacent anatomic spaces, fracture of the maxillary tuberosity, and root fracture. Ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 13 publications
1
15
0
1
Order By: Relevance
“…One systematic review evaluated several risk assessment studies assessing the risk of OAC based on clinical data, panoramic radiography, or cone-beam computer tomography (CBCT) utilizing statistical models. The authors concluded that panoramic radiographies are not reliable for assessing risk factors for OAC compared to CBCT based on current evidence [ 5 ]. We could confirm this finding by applying multiple deep-learning algorithms and letting experts evaluate the preoperative panoramic radiography.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One systematic review evaluated several risk assessment studies assessing the risk of OAC based on clinical data, panoramic radiography, or cone-beam computer tomography (CBCT) utilizing statistical models. The authors concluded that panoramic radiographies are not reliable for assessing risk factors for OAC compared to CBCT based on current evidence [ 5 ]. We could confirm this finding by applying multiple deep-learning algorithms and letting experts evaluate the preoperative panoramic radiography.…”
Section: Discussionmentioning
confidence: 99%
“…The maxillary sinus can have variable anatomy due to maxillary sinus septa, temporary mucosal swelling, previous operations (Caldwell–Luc operation), or tumors [ 4 ]. Two-dimensional radiographic imaging is the standard imaging for routine extraction of maxillary teeth [ 5 ]. Panoramic radiography is the most widely used imaging modality for common oral surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 A limitation of 2-dimensional imaging, however, is the superimposition of anatomical structures. 3 8 Figure 2 is a panoramic radiograph of a 73-year-old man who came in for a routine dental check-up. After the clinical exam was performed, a panoramic image was obtained.…”
Section: Two-dimensional Versus Three-dimensional Imaging In Diagnosing Oacmentioning
confidence: 99%
“…
Oro-antral communication (OAC) is the inevitable connection between the oral cavity and the maxillary sinus. The most reputable cause of the condition is the extraction of maxillary molars due to the close proximity of their roots to the antral floor which is very thin in this area [1,2] . Moreover, periapical infection, large cysts, tumors and trauma can all be potential causes of oroantral communication [3,4] .
…”
mentioning
confidence: 99%